2004
DOI: 10.1002/fam.854
|View full text |Cite
|
Sign up to set email alerts
|

Restraint of fire‐exposed concrete floor systems

Abstract: SUMMARYThis paper describes the numerical analyses of restrained concrete floor slabs exposed to fire. The analyses of the slabs were carried out with the SAFIR finite element program considering a 200 mm thick slab, spanning 5 m between two end supports. The slabs were exposed to the ISO standard fire for up to 4 h and were analysed with pinned and rotationally restrained supports. Different heights of the line of thrust at the supports and different levels of axial restraint were also investigated. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 7 publications
2
23
0
3
Order By: Relevance
“…The program was developed for analysing steel or composite structures, but the shell element in SAFIR has been proven to also accurately predict the fire behaviour of RC slabs [13]. A previous study showed that SAFIR can successfully predict the structural behaviour of hibond slabs (proprietary composite slabs) using a combination of shell and beam elements [14], which is the basic idea behind the proposed model in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The program was developed for analysing steel or composite structures, but the shell element in SAFIR has been proven to also accurately predict the fire behaviour of RC slabs [13]. A previous study showed that SAFIR can successfully predict the structural behaviour of hibond slabs (proprietary composite slabs) using a combination of shell and beam elements [14], which is the basic idea behind the proposed model in this study.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has demonstrated that two-way supported RC slabs have better fire resistance than one-way supported slabs due to the membrane action [13]. Besides, restraint due to the surrounding structure has been proven to have a favourable effect on the performance of the HC floor system in fire [18].…”
Section: Introductionmentioning
confidence: 99%
“…Additional analyses with varying levels of axial restraint increased the fire resistance to over 90 minutes, and over 120 minutes in some cases [2]. The effect of axial restraint on fire resistance depends greatly on the height of the line of action of the restraint force, as discussed by Lim et al [16].…”
Section: Single-bay Beammentioning
confidence: 91%
“…Traditionally, simply supported precast prestressed hollowcore slabs in New Zealand have been widely used as shown in Figure 1 [12], [13]. The simple connection details comprised of the floor unit seated on a mortar bed, core end plugs to prevent concrete from entering the cores, and conventional starter bar reinforcement in the topping slab [1].…”
Section: Simple Connection Detailmentioning
confidence: 99%